Population-level phylogenomic analysis yields insights into species cohesion and population substructure of Lobelia section Lobelia (Campanulaceae) - Grant T. Godden; Andrew A. Crowl; Stephen R. Patten; Princess Abu; Svea Hall; Mark O. Johnston; Douglas W. Schemske; T. Wayne Barger; Miguel A. Pérez-Pérez; Christopher R. Herlihy; Lynda F. Delph; Christopher B. Blackwood; et al. (Molecular Phylogenetics and Evolution, 2025)

Contrasting grazing practices alter plant community trajectories across western Canada’s grasslands with implications for ecosystem function - Timm F. Döbert; Lysandra A. Pyle; Carter Case; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang; Laio Silva Sobrinho; Majid Iravani; Mark S. Boyce (Agriculture, Ecosystems & Environment, 2025)

Contribution of offshore platforms and surrounding habitats to fish production in the Bass Strait, south-east Australia - Matthew Birt; Dianne L. McLean; Mark Case; Samantha Jaworski; Conrad W. Speed; Daniel Pygas; Damon Driessen; Laura Fullwood; Euan Harvey; Brigit Vaughan; Peter I. Macreadie; Jeremy T. Claisse (Continental Shelf Research, 2024)

Regional patterns in demersal fish assemblages among subsea pipelines and natural habitats across north-west Australia - Ronen Galaiduk; Ben Radford; Mark Case; Todd Bond; Michael Taylor; Tim Cooper; Luke Smith; Dianne McLean (Frontiers in Marine Science, 2022)
Regional patterns of fish diversity, abundance, distribution, and assemblage composition are driven by a combination of biotic and abiotic conditions in the marine environment, but these conditions can be altered through anthropogenic activities, such as those associated with oil and gas extraction. The present study utilises data on fish relative abundance and diversity obtained from 1546 baited remote underwater video deployments conducted between 2004 – 2019 in depths of 9 – 170 m across 2000 km of coastline in north-west Australia on natural habitats and subsea pipelines to understand the influence of oil and gas infrastructure on fish assemblages. A total of 450 fish taxa from 56 families was observed, with populations dominated by generalist and invertebrate carnivore taxa. At the regional scale, subsea pipelines had lower diversity (lower taxonomic richness) than natural environments, but possessed a higher abundance of piscivorous and herbivorous fish taxa. Clear patterns in fish assemblage composition were observed in multivariate analyses, reflecting the proximity of oceanic shoals and banks, depth, and to a lesser extent, oil and gas infrastructure. Shallow-water and close to shoals assemblages were characterised by a diversity of site-attached (e.g., wrasses, tuskfish), reef-associated taxa (e.g., emperors). Mesophotic fish assemblages were characterised by commercially important (e.g., goldband snapper), wide-ranging (e.g., sharks) and sand-affiliated (e.g., toadfish, threadfin bream) taxa. Proximity to pipelines and platforms ranked low as predictors in the multivariate analyses suggesting a negligible regional influence of these structures on fish communities in comparison to depth and shoal habitats. Local-scale influences of subsea infrastructure, however, may be important for some fish species (infrastructure vs. immediate surrounds). Our study highlights the influence of abiotic factors on regional-scale patterns in fish assemblage structure across north-west Australia.

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

A Phylogeny and Timescale for Marsupial Evolution Based on Sequences for Five Nuclear Genes - Robert W. Meredith; Michael Westerman; Judd A. Case; Mark S. Springer (Journal of Mammalian Evolution, 2008)

Molecular Evidence for the Last Survivor of an Ancient Kangaroo Lineage - Michael Westerman; Angela Burk; Heather M. Amrine-Madsen; Gavin J. Prideaux; Judd A. Case; Mark S. Springer (Journal of Mammalian Evolution, 2002)

Sectional notes - Devid N. Wright; Mark Kofhnke; J. C. Campbell; W. J. Evans; W. M. Case; C. A. Hexderson; O. D. Burke; John Noonan; Harold L. Bailey; Verney C. Beverley; Harold S. Schaad; J. W. Scannell (American Journal of Potato Research, 1947)